2020
DOI: 10.20517/2574-1225.2019.45
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic value of erythrocyte sedimentation rate levels as a predictor of staple-line leakage in bariatric surgery

Abstract: Aim: Bariatric surgery is an effective treatment for morbid obesity that has inevitable complications including postoperative bleeding and staple-line leakage. Erythrocyte sedimentation rate (ESR) can be a clinical indicator for prediction of leakage. Methods: This retrospective cohort study was done on 1999 patients who underwent sleeve gastrectomy in Erfan Niyayesh Hospital, Tehran, Iran. ESR levels of patients were evaluated in cases which had postoperative leak. Statistical analyses were performed using SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Gastrointestinal leakage usually presents as an immediate postoperative complication following bariatric surgery. 15,17 Therefore, signs and symptoms of leakage, including a drop in hemoglobin levels, hematochezia, hematemesis, or melena, should be considered for further evaluations. 18,19 On the other side, endoscopy is often performed as a routine diagnostic method to investigate of the leakage source.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastrointestinal leakage usually presents as an immediate postoperative complication following bariatric surgery. 15,17 Therefore, signs and symptoms of leakage, including a drop in hemoglobin levels, hematochezia, hematemesis, or melena, should be considered for further evaluations. 18,19 On the other side, endoscopy is often performed as a routine diagnostic method to investigate of the leakage source.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic SG was performed for all individuals based on the standard protocol approved by the American Society for Metabolic and Bariatric Surgery. 15…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic sleeve gastrectomy was performed for all subjects based on the standard protocol under supervision of a specific surgeon with similar tools and same duration of operation. More details on the process of surgery has been published in our recent study (11).…”
Section: Surgical Techniquementioning
confidence: 99%
“…This article [1] has been retracted by authors because there are unresolved issues relating to authorship and contents. All the authors confirmed this retraction.…”
mentioning
confidence: 99%